Pengembangan Model Chatbot Asesmen untuk Membantu Siswa Menguasai Konsep Sistem Ekskresi - Amelia Savitri Zairul; Ana Ratna Wulan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop and evaluate the practicality and effectiveness of a tawk.to-based formative assessment chatbot integrated into Google Sites to support junior high school students' mastery of excretory system concepts. The study used the Research and Development (R&D) method with the ADDIE model and involved eighth-grade students at a public junior high school in Bandung City. Data were collected through pretest-posttest tests, practicality questionnaires, and the User Experience Questionnaire (UEQ). The results showed that the use of the formative assessment chatbot improved students' conceptual mastery with a moderate level of effectiveness. The chatbot was deemed highly practical, particularly in providing automated feedback, supporting concept mastery, and presenting questions based on higher-order thinking skills. However, several technical and visual aspects still require improvement. Overall, the formative assessment chatbot has the potential to be an effective and innovative support medium for biology learning by providing instant feedback and facilitating diagnostic assessments.